Social capital and having a regular family doctor: Evidence from longitudinal data. (January 2019) - Bataineh, Hana; Devlin, Rose Anne; Barham, Vicky
Abstract: Access to a regular source of health-care is problematic for some, irrespective of whether the regime is publicly or privately funded. Yet, evidence shows that access to a regular family doctor improves health outcomes. We are the first to examine the impact of social capital (e.g., tangible support, friends and family) on having a regular family doctor taking into account that social capital may be endogenously determined. Using the Canadian National Population Health longitudinal survey (1994–2010: n = 41, 022) and a dynamic random effects probit model (with and without endogenous initial conditions) we find robust evidence of a statistically significant and positive causal relationship between social capital and the probability of having a regular family doctor. Since past access to a family doctor is a strong predictor of both current and future access, we show that social capital is much more important in helping individuals find a family doctor than for keeping one. Highlights: Social capital increases the likelihood of having a regular family doctor. Men are much more sensitive to living arrangements than are women. Social capital affects the younger (under 40) group much more than the older one. Social capital is instrumental for finding a regular physician, less important for keeping one.